Pengaruh Growth, Cash Ratio, Struktur Kepemilikan Manajerial dan Profitabilitas terhadap Deviden Payout Ratio (DPR) pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) - Widiantari, Ni Kadek; Wahyuni, Made Arie (Universitas Pendidikan Ganesha, 2021)
Abstract This study was aimed at determining the effect of growth, cash ratio, managerial ownership structure and profitability on the dividend payout ratio in mining companies listed on the Indonesian stock exchange. The type of data which used in this study was quantitative data with secondary data. The data analysis technique used in this study was multiple regression analysis with the Classical Assumption Test, the Coefficient of Determination Test, and the T Test. The population of this study was 49 mining companies listed in Indonesian stock exchange with 13 companies qualified in 5 years, so the sample analised was 65 samples. This study used purposive sampling in determining the sample. The results show that Growth has a significant negative effect on the dividend payout ratio. While cash ratio, managerial ownership structure, profitability have a significant positive effect on the dividend payout ratio in mining companies listed on the Indonesian stock exchange. Keywords : Deviden Payout Ratio, Growth, Cash Ratio, Managerial Ownership Structure And Profitabilitas.